Extreme Outliers in the Database for Calculation of Ecological Footprint; The Problems of Grazing Land Footprint as Well as the Fishing Ground Footprint Calculation - Szigeti, Cecília; Borzán, Anita (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2012)
The appreciation of ecological footprint has been increasing since the study by Stiglitz, Sen and Fitoussi’ [Stiglitz et al. 2009]. At the same time, owing to the methodological and standardization problems as well as the shortcomings of data collection, its accuracy can be questioned. In our study, we were looking for countries with a significantly differing from the world average composition of the ecological footprint, with the help of cluster analyses and data from the database used for calculating the ecological footprint index by the Global Footprint Network. Comparing data from two years, we were trying to find answer to the question if the outlier data can trace back to professional errors or data collection problems. Basing on our studies, we can determine a two members group with an outstanding grazing land footprint (Mongolia, Uruguay), which can be considered as outliers according to every examination method. The formation of a stable group characterized by a big fishing ground footprint in 2010 can trace back to an inconsistency in the database, which is proved by the example of Gambia and Norway. In our opinion, a control of outliers is necessary for proper calculation of the EF index every year.